2010
DOI: 10.1111/j.1470-6431.2010.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Globalization vs. localization: global food challenges and local solutions

Abstract: The objective of this study was to examine the effect of global-local interactions on food production and consumption in Ghana, and identify possible local solutions. Primary data were collected using a combination of quantitative-qualitative methods, which included focus group discussions and one-on-one interviews. Approximately 450 household heads were randomly selected and interviewed between August 2007 and August 2008 in Eastern, Central, Upper East and Northern Regions of Ghana. Findings revealed increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…The analysis of the CMA case has shown that the characterization of the foodshed through the three designed indicators: (1) intensity, (2) variety of foodstuffs, and (3) freshness can bring to light the local scale of an LFS. What is advocated here, set against other definitions of "localness" stated hitherto by distance between producers and consumers, social constructions, and cultural elements [31,84,85], is that "local" is the critical convergence of the three scales extracted from the foodshed indicators, namely (1) the intensity scale, (2) the variety scale, and (3) the freshness scale. This implies that local is anchored to the food supply support structure and, concretely, to the area that holds a stronger and more consolidated supply linkage with the urban side.…”
Section: Local Scale For the Local Food Systemsmentioning
confidence: 90%
“…The analysis of the CMA case has shown that the characterization of the foodshed through the three designed indicators: (1) intensity, (2) variety of foodstuffs, and (3) freshness can bring to light the local scale of an LFS. What is advocated here, set against other definitions of "localness" stated hitherto by distance between producers and consumers, social constructions, and cultural elements [31,84,85], is that "local" is the critical convergence of the three scales extracted from the foodshed indicators, namely (1) the intensity scale, (2) the variety scale, and (3) the freshness scale. This implies that local is anchored to the food supply support structure and, concretely, to the area that holds a stronger and more consolidated supply linkage with the urban side.…”
Section: Local Scale For the Local Food Systemsmentioning
confidence: 90%
“…In contrast to the conventional, increasingly delocalized or globalized, and centralized food production chain of the industrialized countries (IPES-Food, 2016, 2018; Ellen MacArthur Foundation, 2019), NAES as a generic model would result in a "glocalized" (e.g., Quaye et al, 2010) and distributed system of food production. In terms of food cultures, it would result in diversification as opposed to the current trend of homogenization (Ritzer, 2013;Clapp, 2016).…”
Section: Network Of Aes (Naes) As a Foundation For A Sustainable Foomentioning
confidence: 99%
“…Direct connections between farmers and consumers in local markets are lost as mega-size corporations with global downstream supermarket distributors gain control of the food market. As global food becomes cheaper, consumers gradually abandon local food and farmers (Wilhelmina et al, 2010;Andree et al, 2014).…”
Section: Introductionmentioning
confidence: 99%